2012
DOI: 10.1002/pbc.24136
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory epidemiological study of Langerhans cell histiocytosis

Abstract: We explored potential risk factors associated with Langerhans cell histiocytosis (LCH) in a predominantly Hispanic population in Los Angeles. Sixty children with LCH (cases) and, 150 randomly selected patients (controls) were interviewed. There was no statistically significant difference between cases and controls in the following: Family history of thyroid disease, smokers in the family, maternal problems during pregnancy, and pesticide exposure. Cases were more likely to report a family history of cancer (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
4
21
1
7
Order By: Relevance
“…The number of paediatric patients was higher than adult patients, which reflects the highest incidence of this disease in the youngest age as previously been observed. 13,14 The median age (34 years) in our adult patients was comparable with previous reports. [15][16][17] There was a striking reduction in the occurrence of LCH with age.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The number of paediatric patients was higher than adult patients, which reflects the highest incidence of this disease in the youngest age as previously been observed. 13,14 The median age (34 years) in our adult patients was comparable with previous reports. [15][16][17] There was a striking reduction in the occurrence of LCH with age.…”
Section: Discussionsupporting
confidence: 85%
“…LCH in elderly subjects is rare, and it has been presented mainly as case reports. 18,19 Although other studies have reported that males were more affected than females, [13][14][15] proportion of male and female patients was similar in our study.…”
Section: Discussionsupporting
confidence: 70%
“…Chez l'adulte, on dispose de peu données quant à la fréquence de la maladie. Schématiquement, l'HL pulmonaire représente 3 à 5 % des pneumopathies infiltrantes diffuses de l'adulte [7,8]. Sa fréquence est vraisemblablement sous-estimée, du fait de son caractère parfois asymptomatique, de la survenue de rémissions spontanées et des aspects parfois peu spé-cifiques des formes très évoluées.…”
Section: éPidémiologieunclassified
“…LCH występuje w każdym wieku, jednak najczęściej dotyczy dzieci (mediana wieku w chwili rozpoznania wynosi 2,5 roku) [3]. W zależności od rodzaju i ilości zajętych narządów, wyróżnia się: postać jednoukładową (zlokalizowaną) i wieloukładową (rozsianą).…”
Section: Wstępunclassified
“…narządów wysokiego ryzyka: wątroby, śle-dziony i szpiku kostnego, której symptomatologia wymaga różnicowania z uogólnioną infekcją i rozrostowymi schorzeniami limfoproliferacyjnymi [5,6]. Występowanie gorączki w przebiegu LCH jest objawem niespecyficznym, spotykanym również w innych chorobach [3].…”
Section: Omówienieunclassified